A transcribed enhancer dictates mesendoderm specification in pluripotency - Michael Alexanian (Nature Portfolio, 2017)
Long noncoding RNAs (lncRNAs) are key regulators of lineage specification during development. Here, the authors investigate remodeling of enhancers and regulation of the lncRNA transcriptome during mesendoderm specification, and identify a pluripotent stage-specific transcribed enhancer controlling adoption of the mesendodermal cell fate.